2018
DOI: 10.1002/hup.2680
|View full text |Cite
|
Sign up to set email alerts
|

Independent elevation of peripheral oxytocin concentrations and reduction in cognitive empathy during 4‐fluoroamphetamine intoxication

Abstract: Objectives 4‐Fluoroamphetamine (4‐FA) is a novel psychoactive substance with a pharmacological profile and reported subjective effects (e.g., empathy) intermediate between 3,4‐methylenedioxymethamphetamine (MDMA) and amphetamine. Studies have shown that MDMA and amphetamine increase emotional empathy without affecting cognitive empathy; MDMA simultaneously leads to elevated levels of oxytocin, unrelated to its behavioral effects. The aim of the present study was to assess the reported enhancement of empathy by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The conclusion reached by these authors was that the effects of 4-FA lie between those of dextroamphetamine and MDMA, which would indicate that the term psychedelic may be somewhat inaccurate in describing the qualitative effects of 4-FA. On average, 4-FA reduced cognitive empathy and did not affect emotional empathy in the 12 volunteers (Dolder et al, 2018b), which stands in contrast to MDMA, which was shown to leave cognitive empathy unaffected and to increase emotional empathy in a study using 118 volunteers (Kuypers et al, 2017). Overall, the subjective effects of 4-FA seem to be tolerated well by most users, as it was found that drug liking and drug wanting had significantly increased during the acute phase of the trial (1-3 h), but that this effect and drug wanting were absent at the 11-h mark (Kuypers et al, 2018b), indicating that 4-FA also does not exhibit significant abuse potential compared with non-halogenated amphetamines.…”
Section: -Fluoroamphetaminementioning
confidence: 80%
“…The conclusion reached by these authors was that the effects of 4-FA lie between those of dextroamphetamine and MDMA, which would indicate that the term psychedelic may be somewhat inaccurate in describing the qualitative effects of 4-FA. On average, 4-FA reduced cognitive empathy and did not affect emotional empathy in the 12 volunteers (Dolder et al, 2018b), which stands in contrast to MDMA, which was shown to leave cognitive empathy unaffected and to increase emotional empathy in a study using 118 volunteers (Kuypers et al, 2017). Overall, the subjective effects of 4-FA seem to be tolerated well by most users, as it was found that drug liking and drug wanting had significantly increased during the acute phase of the trial (1-3 h), but that this effect and drug wanting were absent at the 11-h mark (Kuypers et al, 2018b), indicating that 4-FA also does not exhibit significant abuse potential compared with non-halogenated amphetamines.…”
Section: -Fluoroamphetaminementioning
confidence: 80%
“…As expected for an oral ingestion, it took at least 1 hour (typically 2 hours, range 1−3 hours) to reach maximum concentrations. This was known from oral amphetamine dosing and respected in the design of the time scheme of the psychomotoric tests . It appeared that maximal concentrations were reached sooner in the higher dosing condition (Figure ) but this might be a consequence of the lower subject number.…”
Section: Discussionmentioning
confidence: 95%
“…This was known from oral amphetamine dosing 14,15 and respected in the design of the time scheme of the psychomotoric tests. 2,16,17 It appeared that maximal concentrations were reached sooner in the higher dosing condition (Figure 1) but this might be a consequence of the lower subject number.…”
Section: Pharmacokinetic Properties Of 4-fa and Amphetamine In Serummentioning
confidence: 96%
“…Stimulants also present complex interactions with neuroendocrine molecules, e.g., they increase oxytocin levels, although the latter, as demonstrated for 4-Fluoroamphetamine, might be unrelated to cognitive and emotional behavior and empathy [ 132 ]. Amphetamine-type psychostimulant include derivatives of aminorex, such as 4-methylaminorex (4-MAR) and 4,4′-dimethylaminorex (4,4′-DMAR) [ 133 , 134 ]. Although both are derivatives of aminorex, the former appears as a more typical stimulant, with a high DAT/SERT ratio, while the latter is thought to lead mainly to empathogenic effects [ 125 ].…”
Section: Resultsmentioning
confidence: 99%